Imajinasi Kebangsaan di Nusantara: Suatu Kajian Bibliografis - KAMARUZZAMAN BUSTAMAM AHMAD (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2017)
This article aims to examine the social imaginary toward nationalism from theoritical and bibliographical perspectives. Recently, there has been lack of study on imagined nationalism, after Bennedict Anderson had published Imagined Communities. This study by looking at social imagination and cultural memory, will describe the development of imagined nationalism in Nusantara. It will also survey several literatures on concept of nationalism in the region. It is believed that imagined nationalism in Nusantara has been influenced by many concepts from Western scholars. Thus, study on on this issue by emphasing on cultural memory is still needed. It is argued that it is necessary to conduct more research projects on imagined nationalism in Nusantara by focussing on spirit, cosmol-ogy, system of knowledge, and values among socities.